2010
DOI: 10.1111/j.1365-313x.2010.04433.x
|View full text |Cite
|
Sign up to set email alerts
|

Nematode CLE signaling in Arabidopsis requires CLAVATA2 and CORYNE

Abstract: SUMMARYPlant-parasitic cyst nematodes secrete CLAVATA3 (CLV3)/ESR (CLE)-like effector proteins. These proteins have been shown to act as ligand mimics of plant CLE peptides and are required for successful nematode infection; however, the receptors for nematode CLE-like peptides have not been identified. Here we demonstrate that CLV2 and CORYNE (CRN), members of the receptor kinase family, are required for nematode CLE signaling. Exogenous peptide assays and overexpression of nematode CLEs in Arabidopsis demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 51 publications
1
99
0
Order By: Relevance
“…It has long been known that cyst nematodes secrete peptides that are structural and functional mimics of plant CLAVATA3/ENDOSPERM SURROUNDING REGION-related (CLE) peptides (Wang et al, 2001(Wang et al, , 2005Gao et al, 2003;Lu et al, 2009), with the latter being peptide hormones required for meristem maintenance and vascular differentiation (Fiers et al, 2007). The nematode CLE effectors are required for virulence (Patel et al, 2008), apparently by stimulating both the CLV2 and the CLV1 pathways (Replogle et al, 2011(Replogle et al, , 2013. Similarly, phytopathogenic root-knot nematodes encode peptides similar to plant C-TERMINAL ENCODED PEPTIDEs (CEPs) that are involved in the regulation of cell expansion (Bobay et al, 2013;Tavormina et al, 2015), although their roles in pathogenesis remain unknown.…”
Section: Manipulation Of Rlp and Rlk Signaling By Pathogen Effectorsmentioning
confidence: 99%
“…It has long been known that cyst nematodes secrete peptides that are structural and functional mimics of plant CLAVATA3/ENDOSPERM SURROUNDING REGION-related (CLE) peptides (Wang et al, 2001(Wang et al, , 2005Gao et al, 2003;Lu et al, 2009), with the latter being peptide hormones required for meristem maintenance and vascular differentiation (Fiers et al, 2007). The nematode CLE effectors are required for virulence (Patel et al, 2008), apparently by stimulating both the CLV2 and the CLV1 pathways (Replogle et al, 2011(Replogle et al, , 2013. Similarly, phytopathogenic root-knot nematodes encode peptides similar to plant C-TERMINAL ENCODED PEPTIDEs (CEPs) that are involved in the regulation of cell expansion (Bobay et al, 2013;Tavormina et al, 2015), although their roles in pathogenesis remain unknown.…”
Section: Manipulation Of Rlp and Rlk Signaling By Pathogen Effectorsmentioning
confidence: 99%
“…Plant parasitic nematodes secrete effectors into the host root, including CLAVATA3 (CLV3)/embryo surrounding region-like effector proteins that function as ligand mimics. These effectors interact with the CLV2/CORYNE receptor complex, an interaction that is important to the successful formation of nematode-induced syncytia, which act as feeding sites from which the parasites obtain nutrition (Replogle et al, 2011). However, effectors that modulate flower development have not yet been identified.…”
mentioning
confidence: 99%
“…Since the discovery of CLV3 (Clark et al, 1995;Ito et al, 2006;Kondo et al, 2006;Ohyama et al, 2009), (putative) CLE genes have been identified in dicots, monocots, mosses, and algae (Jun et al, 2008;Oelkers et al, 2008;Miwa et al, 2009;Zhang et al, 2014;Strabala et al, 2014), and they were shown to act on diverse developmental processes, including shoot and root meristem development, nodulation, embryo and endosperm development, regulation of root architecture in response to nutrients, and vascular development (Hobe et al, 2003;Fiers et al, 2005;Hirakawa et al, 2008;Stahl et al, 2009;Jun et al, 2010;Mortier et al, 2010;Lim et al, 2011;Reid et al, 2011;Fiume and Fletcher, 2012;Okamoto et al, 2013;Araya et al, 2014;Richards et al, 2015;T.-T. Xu et al, 2015). Strikingly, plant-parasitic cyst nematodes also secrete CLE-like effector proteins that are required for successful nematode infection (Wang et al, 2010Replogle et al, 2011;Miyawaki et al, 2013). 3D structure modeling demonstrated that CLV3, CLE1, CLE2, and CLE6 shared a similar arch-shaped molecular structure with conserved residues at the C terminus and middle region, suggesting that these regions could be involved in receptor selection and binding .…”
Section: Peptides With Specific Posttranslational Modificationsmentioning
confidence: 99%